2012
DOI: 10.1002/cbdv.201100326
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Volatile Fraction of Polygonum bistorta L. at Different Growing Stages and Evaluation of Its Antimicrobial Activity against Two Major Honeybee (Apis mellifera) Pathogens

Abstract: The composition of the volatile fraction of Polygonum bistorta L. (also known as bistort or snakeroot) was investigated. Fresh aerial parts of this plant species were collected in the Western Italian Alps during the summer at three different phenological stages, namely vegetative, flowering, and fruiting, and steam-distilled in a Clevenger-type apparatus. The oils accounted for 0.004 to 0.010% of the fresh plant material, and their compositions were determined by GC/FID and GC/MS. The composition of the oils d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Agar Well-diffusion Protocol [23] Autoclaved MHA plates were seeded onto the surface with 24 hour old broth culture of different bacteria. Samples were dissolved thoroughly in DMSO and different concentrations were prepared by serial dilution method.…”
Section: Preparation Of Inoculummentioning
confidence: 99%
“…Agar Well-diffusion Protocol [23] Autoclaved MHA plates were seeded onto the surface with 24 hour old broth culture of different bacteria. Samples were dissolved thoroughly in DMSO and different concentrations were prepared by serial dilution method.…”
Section: Preparation Of Inoculummentioning
confidence: 99%
“…According to the extensive literature, different species of the Polygonoideae subfamily are used in traditional medicine for the treatment of various health problems, but data confirming their potential to fight bacterial infections are both scarce and incomplete [11]. Although the antibacterial activities of different PEM and BIO extracts were assessed in a few recent studies, the extracts were typically tested in disk or well diffusion assays, often in concentrations too high (up to 30 mg/mL) to be relevant [12][13][14][15]. Therefore, we re-evaluated the activity of PEM and BIO extracts against several important human pathogens in a more quantitative way and demonstrated that the BIO extract has moderate antibacterial activity against Staphylococcus aureus with the minimum inhibitory (MIC) and minimum bactericidal (MBC) concentrations of 156 µg/mL and 312 µg/mL, respectively, but weak bactericidal activity against Pseudomonas aeruginosa PAO1 with MIC of 1 mg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, because EOs affect different targets, no cases of bacterial resistance or adaptation have been detected in contrast to the use of antibiotics . Several EOs proved to be effective for controlling A. mellifera diseases such as AFB . EOs of the Argentinian native aromatic plants Acantholippia seriphioides , Artemisia absinthium , Artemisia annua , Aloysia polystachya , Heterothalamus alienus , Lepechinia floribunda , Satureja odora, and Wedelia glauca , presented antimicrobial activity against P .…”
Section: Introductionmentioning
confidence: 99%